Methodology for Lidar Monitoring of Biomass Burning Smoke in Connection with the Land Cover - Adam, Mariana; Fragkos, Konstantinos; Solomos, Stavros; Belegante, Livio; Andrei, Simona; Talianu, Camelia L.; Marmureanu, Luminita; Antonescu, Bogdan; Ene, Dragos; Nicolae, Victor; Amiridis, Vassilis (My University, 2022)
Lidar measurements of 11 smoke layers recorded at Măgurele, Romania, in 2014, 2016, and 2017 are analyzed in conjunction with the vegetation type of the burned biomass area. For the identified aerosol pollution layers, the mean optical properties and the intensive parameters in the layers are computed. The origination of the smoke is estimated by the means of the HYSPLIT dispersion model, taking into account the location of the fires and the injection height for each fire. Consequently, for each fire location, the associated land cover type is acquired by satellite-derived land cover products. We explore the relationship between the measured intensive parameters of the smoke layers and the respective land cover of the burned area. The vegetation type for the cases we analyzed was either broadleaf crops or grasses/cereals. Overall, the intensive parameters are similar for the two types, which can be associated with the fact that both types belong to the broader group of agricultural crops. For the cases analyzed, the smoke travel time corresponding to the effective predominant vegetation type is up to 2.4 days.
Keywords: biomass burning; ERA5; FLEXPART; HYSPLIT; land cover; lidar; MODIS